Fungal Sinusitis: Fact or Fiction?. (2nd September 2014) - Katzer, Cara M.; Bhalla, Vidur; Horvat, Rebecca T.; Tawfik, Ossama W.; Beahm, D. David; Robinson, Ann B.; Hoover, Larry A.
Abstract : Objectives: Participants should be able to: (1) Recognize chronic fungal sinusitis based on clinical examination and radiologic imaging; (2) Analyze the implications of nasal flora contents in suspected chronic fungal sinusitis patients; and (3) Implement surgical and medical treatment of chronic fungal sinusitis. Methods: A retrospective review of the senior author's patients from 1990 to 2014 was completed in which 50 immunocompetent patients thought to have evidence of fungal sinusitis were identified by the following criteria: Classic "high density" material seen on computed tomography (CT), fungal mycelium seen at surgery/fungal smears, and "Fig Newton" material visualized endoscopically in sinuses. Endoscopic surgery was performed on patients with emphasis to widely open sinuses and trim turbinates, allowing postoperative access to affected areas. Intraoperatively, material from sinus cavities was sent for microbiological and pathological analysis. Postoperatively, patients used saline irrigations to remove debris and potent topical steroids to reduce mucosal reactivity and edema. Antifungal agents were not employed. Regular debridements were carried out in the clinic until healing was complete. Results: Fungus was present in 29% of cultures/smears, while staphylococcus, pseudomonas, and other organisms were present in 44%. Nasal sinus mucosa returned to normal appearance in the majority of patients with topical treatment. Some patients with a strong allergy history had persistence of hypertrophic mucosa. A pulsed course of oral prednisone generally resolved this. Conclusions: Wide surgical drainage of affected sinus areas in combination with saline/acetic acid irrigations and topical steroids were successful in nearly all patients without the use of antifungal agents.